Long-Term Exposure to Sulfur Dioxide Before Sensitization Decreased the Production of Specific IgE in HDM-Sensitized Allergic Rhinitis Mice - Ye M; Liu H; Li H; Liu Q; Zhou Z; Wang T; Tan G (Dove Medical Press, 2022)
Maoyu Ye,1 Honghui Liu,1 Honglei Li,2 Qian Liu,1 Zheng Zhou,1 Tiansheng Wang,1 Guolin Tan1 1Department of Otolaryngology-Head Neck Surgery, Third Xiangya Hospital, Central South University, Changsha, People's Republic of China; 2Department of Otolaryngology-Head Neck Surgery, People's Hospital of Deyang City, Deyang, People's Republic of ChinaCorrespondence: Guolin Tan; Honghui Liu, Department of Otolaryngology - Head and Neck Surgery, Third Xiangya Hospital, Central South University, Changsha, People's Republic of China, Email guolintan@csu.edu.cn; honghuiliu@csu.edu.cnBackground: Exposure to atmospheric pollutants is closely associated with the occurrence of allergic rhinitis (AR). However, the role of sulfur dioxide (SO2) in promoting allergic inflammation in AR is poorly understood. Our study aims to investigate the effect of SO2 on allergic inflammation in house dust mite (HDM)-sensitized mice.Methods: Thirty mice were randomly divided into five groups: the control, AR model, AR model exposed to SO2, AR model with long-term SO2 exposure, and SO2-treated control groups. Nasal symptom score was recorded. The serum HDM specific IgE (sIgE) was measured by enzyme-linked immunosorbent assay. Expression of Th1/Th2/Th17 cytokines in nasal mucosa was detected by immunohistochemistry and quantitative PCR. Expression of a low-affinity sIgE receptor (CD23) on B lymphocytes in nasal mucosa was assessed by immunofluorescence.Results: SO2 increased not only nasal symptom score but also the number of infiltrating eosinophils and expression of Th1/Th2/Th17 cytokines in nasal mucosa of HDM-sensitized AR mice. Furthermore, SO2 increased the serum sIgE level in AR mice. However, long-term SO2 exposure decreased the serum sIgE level in AR mice. Moreover, long-term SO2 exposure decreased CD23+ B lymphocytes in the nasal mucosa.Conclusion: SO2 exposure aggravated nasal symptom, serum sIgE level, eosinophil infiltration, and Th1/Th2/Th17 inflammation in AR mice. However, the serum sIgE level could be lowered by long-term SO2 exposure. This inhibitory effect of SO2 on IgE production may be suppressed by CD23+ B lymphocytes.Keywords: allergic rhinitis, air pollution, sulfur dioxide, inflammation